Apache - Bird, Frederick A. (Minneapolis, Minnesota : Checkerboard Library, 2022)
Introduces young readers to the Apache people, their traditional ways of life, including social structure, homes, food, art, clothing and more, their contact with Europeans, and how the Apache are keeping their culture alive today.
Homelands -- Society -- Homes -- Food -- Clothing -- Crafts -- Family -- Children -- Traditions -- War -- Contact With Europeans -- Geronimo -- The Apache Today.
School Library Journal, April 2022
Includes index.
5.8
3-6
820L
Keywords: Apache Indians -- Juvenile literature; Indians of North America -- Juvenile literature; Indigenous peoples -- Social life and customs -- Juvenile literature; Ethnology -- Juvenile literature; Apache Indians; Indians of North America; Indigenous peoples -- Social life and customs; Ethnology